Specific binding of formylated initiator-tRNA to Escherichia coli RNA polymerase. - Pongs, O (1976)
E. coli fMet-tRNAfMEet and E. coli RNA plymerase (RNA nucleotidyltransferase; EC 2.7.7.6; nucleoside-triphosphate:RNA nucleotidyltransferase) form a 1:1 complex with an apparent association constant of 9.0 X 10(6)M-1 at 37 degrees. The affinity of polymerase to tRNA depends on the tRNA as well as the formyl methionine moiety. Core polymerase has a greatly reduced affinity for initiator tRNA. Optimal binding conditions are similar to those that are also optimal for binding initiator tRNA to ribosomes. Binding of initiator tRNA to polymerase stimulates the transcription of lambda plac DNA, as determined in a crude cell-free system for beta-galactosidase (EC 3.2.1.23; beta-D-galactoside galactohydrolase) synthesis as well as in a highly purified transcription system.